Implantação da Residência Médica e Multiprofissional em Saúde da Família em um município paulista: percepção de residentes da primeira turma (2014-2016) (Revista Brasileira de Pesquisa em Saúde/Brazilian Journal of Health Research, 2018)
Implementation of Medical and Multi-professional Residency in Family Health in Health in a São Paulo municipality: first class residents’ perception of (2014-2016)